Cucurbitacin D Induces G2/M Phase Arrest and Apoptosis via the ROS/p38 Pathway in Capan-1 Pancreatic Cancer Cell Line. (22nd September 2020) - Kim, Myeong-Sun; Lee, Kangwook; Ku, Jin Mo; Choi, Yu-Jeong; Mok, Kyungyul; Kim, Doori; Cheon, Chunhoo; Ko, Seong-Gyu
Abstract : Pancreatic cancer has a poor prognosis with a five-year survival rate of less than 10%. Moreover, chemotherapy is mostly rendered ineffective owing to chemotherapy resistance and cytotoxicity. Therefore, the development of effective therapeutic strategies and novel drugs against pancreatic cancer is an urgent need. Cucurbitacin D (CuD), a plant steroid derived from Trichosanthes kirilowii, is an anticancer agent effective against various cancer cell lines. However, the anticancer activity and molecular mechanism of CuD in pancreatic cancer remain unknown. Therefore, we aimed to investigate the anticancer activity and molecular mechanism of CuD in the human pancreatic cancer cell line, Capan-1. CuD induced cell cycle arrest at the G2/M phase, apoptosis, and reactive oxygen species generation in Capan-1 cell line. In addition, CuD induced the activation of the p38 MAPK signaling pathway that regulates apoptosis, which was also inhibited by N -acetyl-L-cysteine and the p38 inhibitor SB203580. These data suggest that CuD induces cell cycle arrest and apoptosis via the ROS/p38 pathway in Capan-1 pancreatic cancer cell line; hence, CuD is a promising candidate that should be explored further for its effectiveness as an anticancer agent against pancreatic cancer.